Mapping out Liberating Traces of the Fun of Undisciplined Play: A Search for an Alternative Aesthetic in Graffiti - Alam, Sohaib; Ahmad, Farhan; Khalid, Sadaf; Shubhi (Journal of Education Culture and Society, 2022)
Aim. The present study primarily engages with graffiti as a tactic of the weak who find pleasure in scandalising the dominant discourse. The prime focus here will be on the pleasure as resistance, on the construction of an alternative space into the dominant space, and on the multiple forms of evasive and resisting techniques through which the subordinate asserts their power. Thus, Graffiti can be read as a popular text, a signifying construct of potential meanings and pleasures for the subordinate. Concept. Conceptualised as the undisciplined play of the subordinate people that resists or evades hegemonic forces and a radical reimagining of the neo-liberal spaces, Graffiti has become a major expression of popular culture in recent times. The paper uses many such stances where the lateral thinking of the power helps to challenge the disciplinary discourses of the dominant. Results and Conclusion. The paper offers a popular reading of graffiti that opens up the way to escape control, scandalise top-down power and to assert bottom-up power at the micro-level. The real pleasure lies in scandalising the dominant discourse. Graffiti is read here as self-assertion of the marginalised who acquire public visibility and power through graffiti creation. Originality. The originality of the study depends on reviewing the manipulative actions of people in everyday lives and how this undisciplined play provides them with the opportunity to subvert the system and to escape social control. It supports the idea that the subordinate possesses transgressive deviation in relation to the everyday continuum.